2018
DOI: 10.1159/000492901
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter Exposure During Perinatal Life Results in Impaired Glucose Metabolism in Adult Male Rat Offspring

Abstract: Background/Aims: Particulate matter (PM) is an important risk factor for immunological system imbalance due to its small size, which can reach more distal regions of the respiratory tract, independently of its chemical composition. Some studies have suggested that PM exposure is associated with an increased incidence of diabetes, especially in industrialized urban regions. However, studies regarding the effects of PM exposure during perinatal life on glucose metabolism are limited. We tested whether exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
6
0
2
Order By: Relevance
“…A rat model study by Yi et al 2017 showed that exposure to PM 2.5 has reduced pancreas glucose transporter2 (GLUT2) expression as one of the important factor of glucose intolerance as well as pancreatic methane dicarboxylic aldehyde (MDA) and suggested that inflammation and oxidative stress response related exposure to PM 2.5 could increase risk of pancreatic impairment and glycemic consequence [65]. Other animal studies also reported that exposure to air pollution had been associated with increase in insulin immunodensity of pancreatic islets [66,67]. Finally, changes in glucose homeostasis in healthy pregnant women might be due to the metabolic induction change in the hypothalamus [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…A rat model study by Yi et al 2017 showed that exposure to PM 2.5 has reduced pancreas glucose transporter2 (GLUT2) expression as one of the important factor of glucose intolerance as well as pancreatic methane dicarboxylic aldehyde (MDA) and suggested that inflammation and oxidative stress response related exposure to PM 2.5 could increase risk of pancreatic impairment and glycemic consequence [65]. Other animal studies also reported that exposure to air pollution had been associated with increase in insulin immunodensity of pancreatic islets [66,67]. Finally, changes in glucose homeostasis in healthy pregnant women might be due to the metabolic induction change in the hypothalamus [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…As the onset of metabolic disorders steadily increases in children and young adults, there is a great need to understand this etiology. Significant associations have been found between prenatal exposure to environmental pollutants and the heightened risk for metabolic impairments ( 69 , 71 , 73 , 125 ). One potential mechanism is an increase in neuroinflammation, particularly affecting the hypothalamus.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…A rat model study by Yi et al 2017 showed that exposure to PM 2.5 has reduced pancreas glucose transporter2 (GLUT2) expression as one of the important factor of glucose intolerance as well as pancreatic methane dicarboxylic aldehyde (MDA) and suggested that in ammation and oxidative stress response related exposure to PM 2.5 could increase risk of pancreatic impairment and glycemic consequence [65]. Other animal studies also reported that exposure to air pollution had been associated with increase in insulin immunodensity of pancreatic islets [66,67]. Finally, changes in glucose homeostasis in healthy pregnant women might be due to the metabolic induction change in the hypothalamus [68,69].…”
Section: Biological Plausibilitymentioning
confidence: 99%